Flying Bombs over England - Bates, H. E.; Edited By Ogley, Bob (Westerham Froglets, 1994)
Recreates the atmosphere of life 50 years ago when Germany let loose its V1s and V2s. The book explains the brilliant German engineering skills behind this last-ditch orgy of terror, and describes how they were finally repulsed by the front-line boys and girls in this new Battle of Britain.
Include Illustrations and Index
Keywords: World War (1939-1945)